United States : Financial Sector Assessment Program-Technical Note-Systemic Risk Oversight and Systemic Liquidity. - International Monetary Fund. Monetary and Capital Markets Department (Washington, D.C. : International Monetary Fund, 2020)
The heterogeneity of the United States (U.S.) financial markets and complex regulatory and supervisory institutional setup in the United States underscore the importance of enhancing systemic risk oversight and building effective macroprudential tools. An effective framework would encompass identification and prioritization of system-wide risks and vulnerabilities to spur timely policy action. Structures that ensure interagency sharing of information, identify possible emerging regulatory gaps, obtain a good overview of systemic risks, and develop a cooperative framework to address identified threats to financial stability would be necessary components of such a framework. This Technical Note reviews those processes in the United States, as well as examining the issues of systemic liquidity.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet